Geotechnical earthquake engineering seismic slope safety - Sarma, S. K. (2021)
The aim of Geotechnical earthquake engineering is two fold: 1. The study of geotechnical materials as soils and rocks under seismic loading conditions. 2. Analysis and design of earth structures and foundations including soils layers and slopes subjected to earthquakes. The first part of the course gives an overview of dynamic soil properties including the liquefaction phenomenon. Response analysis of soil layers give an idea of how the local soil conditions effect the ground motion at a site. Seismic response and stability of earth dams show the simplified design analysis technique. Seismic earth pressures and the seismic design of foundations are also included.